PROTECTING COPYRIGHT ON CONTENT EXCHANGE PLATFORMS, LIKE FACEBOOK, INSTAGRAM, OR YOUTUBE (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
The rapid growth of content sharing sites such as Facebook, Instagram, and YouTube has revolutionized user creation, dissemination, and consumption of digital content. However, this has also brought along with-it critical problems in copyright protection. This article addresses the issues and solutions relating to the protection of intellectual property rights on the sites. It addresses the prevailing legal systems, the function of the platform policy, and the effectiveness of technological measures in averting copyright infringement. Based on case studies and experiences, the article seeks to offer insights on the ongoing battle between creators and copyright violators and end up proposing means of enhancing copyright protection in the digital world.